Intellectuals, Canon and Literature in the Anti-Fascist Cultural Magazines of the Spanish Civil War (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2023)
The coup d'état by Francisco Franco in July 1936 was a turning point for the anti-fascist republican intelligentsia. During the three years of the Civil War, intellectuals created associations and cultural magazines to defend the Spanish Second Republic.These publications include El Mono Azul, Hora de España and Meridià, the first two written in Spanish and the third one in Catalan. In its pages, the writers defined what it meant to be a left-wing intellectual opposite to an anti-intellectual; the relationship between Spanish and Catalan anti-fascist intellectuals; the kind of literature representative of the republican people, that is, what was the literary canon that responded to a democratic culture and contrary to fascism; the course of the war; as well as the celebration of the Second International Congress of Writers for the Defense of Culture.Therefore, on one hand we want to explain the cultural deployment carried out by Spanish and Catalan intellectuals during the Civil War. And, on the other hand, we want to show the similarities and differences between these intellectuals when defining what characterises the left-wing intellectual and anti-fascist literature in the articles published in El Mono Azul, Hora de España and Meridià.